PREFERENSI KONSUMEN TERHADAP SAYURAN HIDROPONIK DI SEBELAS MARET HIDROPONIK SURAKARTA - Setyarini, Agung -; Arianti, Yoesti S.; Retnaningsih, Nugraheni (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2024)
Hydroponic vegetables are one of the increasingly popular horticultural products. The specialty of hydroponic vegetable products is that they are fresher and cleaner than conventional vegetables. The purpose of this research is to analyze consumer preferences, and determine the order of attributes that are the main considerations for consumers of hydroponic vegetables. The method of determining the location was done purposively at Sebelas Maret Hydroponics Surakarta. The sampling method is non probability sampling with a convenience sampling approach of 33 respondents with the criteria of having bought and consumed hydroponic vegetables produced by Sebelas Maret Hydroponics. Data analysis method with Fishbein's multi-attribute model. The results showed that consumer preferences for hydroponic vegetables are vegetables that has physical conditions of leaves that are wide, not torn, not perforated, intactand not broken. The condition of freshness of vegetables that are harvested directly, with bright light green vegetable colors, vegetable flavors that are different from conventionally cultivated vegetables. The packaging of vegetables is closed and transparent, and there is a label on the packaging. The main attributes considered by consumers in purchasing hydroponic vegetables are the level of freshness, vegetable taste, physical condition of vegetable leaves, vegetable color, packaging and labels.